2013
DOI: 10.5505/1304.7361.2013.57689
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Practices of Turkish Emergency Physicians: A National Survey

Abstract: SUMMARY ObjectivesThe objective of this study is to ascertain the mechanical ventilation management skill perception levels of emergency physicians in Turkey as well as to determine the infrastructural condition of ED in Turkey with respect to mechanical ventilation. MethodsWe distributed a survey to all emergency physicians in Turkey. The contents of the survey consisted of 4 main areas that paralleled the objectives of the study. (1) Socio-demographic characteristics, (2) the situation of the personnel and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Our survey response rate was similar to previous online survey studies for EM physicians in Turkey but lower for national survey studies for the same population. 13,16,19,20 TRH EM residency training programs started later than UH residency programs, and accordingly the majority of the participants declared that they had their residency training at a university hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey response rate was similar to previous online survey studies for EM physicians in Turkey but lower for national survey studies for the same population. 13,16,19,20 TRH EM residency training programs started later than UH residency programs, and accordingly the majority of the participants declared that they had their residency training at a university hospital.…”
Section: Discussionmentioning
confidence: 99%
“…These subcommittees developed to support scientific improvement within the field, and disaster preparedness has been studied among Turkish health-care workers and found to be suboptimal. [10][11][12][13][14][15][16] Surveys of health-care workers at state hospitals in the city of Kocaeli found rates of disaster preparedness training of health-care professionals to be between 20% and 50%. 12,17 These studies also revealed that lack of training was an important source of anxiety for health-care workers possibly involved in disaster response.…”
mentioning
confidence: 99%